'Demystifying' the encounter with adolescent patients: a qualitative study on medical students' experiences and perspectives during training with adolescent simulated patients. Issue 1 (1st January 2021) - Takeuchi, Yusuke Leo; Bonvin, Raphaël; Ambresin, Anne-Emmanuelle
ABSTRACT: Training with adolescent simulated patients (ASP) is increasingly recognized as an effective form of teaching interviewing skills with adolescent patients. Beyond the acknowledged effectiveness and satisfaction of training with ASP, little is known on medical students' actual experience and specific learning needs related to simulated encounters with ASP, as well as factors influencing their learning experience. The aim of this study was an in-depth exploration of medical students' perspectives about training with ASP. Using a qualitative design with grounded theory methods, we conducted in-field observation of training sessions with ASP and individual interviews with eighteen fourth-year medical students participating in training. When provided with an actual experience in a simulated setting, students go through a process of anticipating then modulating the challenge of the encounter with an adolescent patient. This challenge is influenced and modulated within 3 main dimensions: preconceptions about adolescents, level of experience with adolescent patients and professional distance. This process is also influenced by how students perceive and cope with the educational setting. Training with ASP, as a first concrete experience of an adolescent consultation, is an opportunity to address important aspects of students' attitudes towards adolescent patients such as students' preconceptions, personal experiences and feelings that could influence the doctor-patient relationship later on. Training should focus on ways to reflect upon and handle such attitudes and the emotional resonance experienced by medical students.